2021
DOI: 10.3389/fonc.2021.631943
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatic Steatosis Predicts Higher Incidence of Recurrence in Colorectal Cancer Liver Metastasis Patients

Abstract: Purpose: Colorectal liver metastasis (CRLM) is the major cause of death due to colorectal cancer. Although great efforts have been made in treatment of CRLM, about 60–70% of patients will develop hepatic recurrence. Hepatic steatosis was reported to provide fertile soil for metastasis. However, whether hepatic steatosis predicts higher incidence of CRLM recurrence is not clear. Therefore, we aimed to determine the role of hepatic steatosis in CRLM recurrence in the present study.Methods: Consecutive CRLM patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 53 publications
(72 reference statements)
0
19
0
Order By: Relevance
“…Of the 16 studies selected for full-text analysis, seven studies were excluded with reasons. A total of nine studies fulfilled the eligibility criteria and were included in this review ( 12 – 15 , 18 22 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 16 studies selected for full-text analysis, seven studies were excluded with reasons. A total of nine studies fulfilled the eligibility criteria and were included in this review ( 12 – 15 , 18 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…Irrespective of the etiology, in many patients, the disease gradually progresses to steatohepatitis and cirrhosis resulting in attenuated liver metabolic function and inflammation. Such deranged liver histology provides a fertile ground for seeding and colonization of CRC metastatic cells ( 12 ). To date, many studies have examined the effect of hepatic steatosis on outcomes of CRLM, however, with conflicting results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, liver microenvironments are undeniable components for metastasis. Several clinical studies have reported that pathological conditions such as hepatic steatosis, inflammation and fibrosis accelerate colon-liver metastasis ( Kondo et al, 2016 ; Chen et al, 2021 ). These pathologic alterations in hepatic tissues make the liver microenvironment favorable for liver metastasis, as evidenced by animal studies ( Matsusue et al, 2009 ; Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…4 Another application of DECT material decomposition concerns fat quantification, which has mainly been applied to detect hepatic steatosis as in the highly prevalent nonalcoholic fatty liver disease. 5 Nonalcoholic fatty liver disease can progress to nonalcoholic steatohepatitis (NASH), which negatively influences survival in a variety of entities, for example, cancer, 6,7 or after surgery. 8 It is also a risk factor for hepatocellular carcinoma 9 and the third most common cause of liver transplant.…”
mentioning
confidence: 99%